Compost(able) Research at Longwood Gardens. Issue 1 (1st January 2013) - Taylor, Matt
Abstract : Longwood Gardens in Kennett Square, PA has a strong commitment to sustainability. All organic waste produced on site is either composted or treated and does not leave the property. Longwood's composting facility produces over 3500 cubic yards of compost, mulch and leaf mold per year. In order to use compost and compostable products effectively Longwood performs research in these areas. Compost as a growing substrate component. Peat moss is the primary substrate component used in the greenhouse industry. The inherent pH of peatmoss can range from 3.0 to 4.0 and is typically increased to a suitable pH with the addition of limestone. Compost is a product that can also be used as substrate component and has a high inherent pH of 6.0 to 8.0. When using compost as a substrate component lime rates must be reduced or eliminated. The objective was to determine the resulting pH of substrates with varying amounts of limestone and compost. The experiment was a factorial design with five compost rates (0, 10, 20, 30, and 40% by volume), four limestone rates (0, 1.2, 2.4, and 3.6 g/liter substrate) with five replications. Three batches of each compost type were tested with this experimental design giving a total of 6 experiments. The substrate consisted of 25% pinebark, 5% calcine clay, 15% vermiculite, 15% perlite with the remaining 40% consisting of peat and/or compost based on the treatments. With 0 lime, initial substrate pH increased from 4.5 to 6.7 as compost rate increased. This trend occurred at all other lime rates, which had pH ranges of 5.2‐6.9, 5.6‐7.0 and 6.1‐7.1 for rates of 1.2, 2.4, and 3.6 g/liter substrate, respectively. These data indicate substrate pH was significantly affected by both compost and lime treatments. Growers who use composts in their substrate mix will have to adjust lime rates accordingly to achieve the target pH. Properties of biodegradable containers. Biodegradable containers fall into two categories: compostable, which are designed to be removed from the rootball before the final planting and plantable, which are designed to be left intact on the rootball and planted directly into the field, landscape bed or final container where roots will grow through the container walls. Longwood Gardens, Louisiana State University and University of Arkansas conducted research to determine several properties of these relatively new container types, which included peat, Fertil, Cowpots, coconut fiber, Strawpots, OP47, paper, rice hull and plastic (control). Plastic containers had the highest wall strength followed by paper containers, while peat, Cowpot and Fertil containers had the lowest wall strengths. Neither in the greenhouse or the landscape were there any significant trends on growth of vinca, geraniums or impatiens. After 8 weeks in the outdoor beds, Cowpot containers had the highest level of decomposition while Peat, Strawpot and Fertil containers had lower levels of decomposition. Furthermore, cocofiber containers degraded the least. To produce a geranium crop, Fertil and peat containers required the most water and this amount was about double the amount of water compared to plastic. Container strength, biodegradation and water use varied among the different types of biocontainers tested. Fertil, peat and Cowpot containers had wall strengths low enough to make handling difficult and also had higher water requirements. However, these biocontainers were some of the fastest to decompose in the landscape. Depending upon the geographic location, crop, cultural conditions and post production handling, different biocontainer properties will be more or less important. Growers wanting to improve sustainability by switching to biocontainers will need to evaluate which of the properties are the most significant and choose a biocontainer that fits best into their operation.